Cancer/testis antigen PASD1 silences the circadian clock - Michael, Alicia K. (Mol Cell, 2015)
The circadian clock orchestrates global changes in transcriptional regulation on a daily basis via the bHLH-PAS transcription factor CLOCK:BMAL1. Pathways driven by other bHLH-PAS transcription factors have a homologous repressor that modulates activity on a tissue-specific basis, but none have been identified for CLOCK:BMAL1. We show here that the cancer/testis antigen PASD1 fulfills this role to suppress circadian rhythms. PASD1 is evolutionarily related to CLOCK and interacts with the CLOCK:BMAL1 complex to repress transcriptional activation. Expression of PASD1 is restricted to germline tissues in healthy individuals, but can be induced in cells of somatic origin upon oncogenic transformation. Reducing PASD1 in human cancer cells significantly increases the amplitude of transcriptional oscillations to generate more robust circadian rhythms. Our results describe a function for a germline-specific protein in regulation of the circadian clock and provide a molecular link from oncogenic transformation to suppression of circadian rhythms.